The Role of Transformational and Transactional Leadership on Job Satisfaction of Millennial Teachers : A CB-SEM AMOS Analysis - Agus Purwanto; Anwar Sulaiman (Faculty of Science and Technology University of Pramita Indonesia, 2023)
The purpose of this study was to analyze the relationship between transformational leadership and teacher job satisfaction, transactional leadership and teacher job satisfaction. This research method is a quantitative survey. The data collection technique in this study used an online questionnaire technique which was designed using a Likert scale of 1 to 7 and distributed to 560 teachers selected by the simple random sampling method. This data processing tool uses Structural Equation Modeling (SEM) using AMOS (Analysis of Moment Structure) version 26. Before conducting data analysis, the validity and reliability of the questionnaire used is tested first. To measure its validity, the score of each question item is used which is correlated with the total item score in one variable. After testing the validity and reliability, then performed data analysis. Analysis and interpretation of data is carried out to answer the problems that have been formulated and answer the hypotheses. In this study, data analysis used Structural Equation Modeling (SEM) with AMOS software. The results of this study are that Transformational leadership has a significant effect on teacher job satisfaction and Transactional leadership has a significant effect on teacher job satisfaction.